Pandemia de Covid-19 e SUS: dimensões das políticas públicas em saúde no Amazonas - Lopes, Lara Suellen Bezerra (2023)
This dissertation aims to analyze the extension of the Unified Health System (SUS) in public health policies, based on the structure of how it was developed in the period of the Covid-19 pandemic in the state of Amazonas, especially in Manaus. The conception of the Unified Health System (SUS) is an important landmark for health in Brazil, since it brought improvements in the rates through the creation of programs to reduce and even eradicate some diseases. A public policy is essential to operate in the formulation of an emerging problem with the objective of reducing or solving it. In the current scenery, SUS and public health policies have taken a leading role in the social context faced with the pandemic caused by the etiologic agent SARS-CoV-2, the new coronavirus or popularly known as Covid-19. To carry out this research, we initially attended to a bibliographical research to support the documental analysis in available sources of the official government documents, websites, articles, minutes, reports. References of André Cellard were used for this reflexive movement and analysis. Amazonas, a state with peculiar properties, was the first state to collapse in the area of public health in Brazil and experienced difficult moments with thousands of deaths related to the new coronavirus. It was observed that during this period, the public policies formulated were not endowed with the moment experienced by the pandemic, face of the expressive increase of cases and deaths in a short period, and the relaxation of bureaucratic measures that were not in accordance with the conditions presented. by the coronavirus. In addition, the traditional peoples confronted difficulties that overcame the adversities imposed by Covid-19. The results found in this qualitative research can contribute to understand the dimension of the actions taken by the government of Amazonas, discussing the practical effects, the pros and cons of these measures, being able to contribute as a technical support for the formulation of regional public policies, providing actions to minimize the impacts left by the pandemic